A FEASIBILITY STUDY OF SOLAR ENERGY-TECHNO ECONOMIC ANALYSIS FROM AKSARAY CITY, TURKEY - Taner, T.; Dalkilic, A. S. (YILDIZ TECHNICAL UNIV, 2019)
This study posed a feasibility study of solar energy-techno economic analysis that was investigated for 20,000 m(2) area of Aksaray city from Turkey. The result of a solar energy radiation production was found to be 1.65 million [kWh/m(2) year]. The profit of solar energy plant was determined about 501,825 [$/y]. A simple payback period time was found to be 4.5 [y]. The aim of the study is to indicate building solar energy plant that can be efficiently for Aksaray city. Since a solar energy plant can be a feasible plant for Yapilcan village, Aksaray city that is near the power line local area network. These results figure out very efficient result for building solar energy plant to Yapilcan village, Aksaray city from Turkey.
Keywords: Renewable Energy; Solar Energy; Techno Economic Analysis; Energy; SYSTEM; ANKARA; PANELS; Thermodynamics